Regime shift to extensive valley glaciations over High Mountain Asia during the Early-Middle Pleistocene - Qing Yan; Lewis A. Owen; Ting Wei; Philip D. Hughes; Xiaohan Kong; Nanxuan Jiang; Jinzhe Zhang; Zhongshi Zhang; Huijun Wang (Nature Communications)
Abstract In contrast to the well-established onset of Northern Hemisphere high-latitude glaciation at ~2.7 Ma, the timing and drivers of the intensified glaciation over High Mountain Asia (HMA) remain elusive, as glacial geologic evidence within this region is inherently fragmentary. Here, we offer a spatiotemporally complete view of glacier behavior over HMA spanning the last 3 Ma using transient climate-glaciation simulations to address this challenge. We illustrate that intensified glaciations with expanded ice caps and widespread valley glaciation began at ~0.9 Ma over the monsoonal-influenced southern HMA confirmed by the glacial sediments, whereas the intensification started earlier (~1.5 Ma) over the westerly-influenced western HMA, with a further intensification at ~1.0–0.9 Ma, supported by paleoenvironmental proxies. The intensification of glaciation masks obvious shifts in the amplitude and pacing of glacier variability (e.g., the establishment of the 100-ka cycle) and induces larger environmental perturbations, which are in line with geologic evidence and largely linked with the long-term global cooling during the mid-Pleistocene transition.